Leadership in Action: Through a New Lens: A Talk with Margaret J. Wheatley - Alexander, John (Center for Creative Leadership, 2001)
Margaret J. Wheatley writes, teaches, and speaks about radically new ideas for organizing and leading in chaotic times. CCL president John Alexander interviewed Wheatley during the third annual Friends of the Center Leadership Conference in Kansas City, Missouri.